Pituitary adenoma apoplexy: Review of personal series - Ricciuti, Riccardo; Nocchi, Niccolò; Arnaldi, Giorgio; Polonara, Gabriele; Luzi, Michele (Asian Journal of Neurosurgery, 2018)
Background: Pituitary apoplexy is a life-threatening event with unspecific clinical background and no standardized treatment. Materials and Methods: The authors retrospectively analyzed seventeen patients affected by pituitary adenoma apoplexy and treated in a 10-year period. Thirteen patients underwent surgery through transsphenoidal route while four patients have been treated conservatively. Results: The endoscopic surgical procedure showed a better result in term of complete removal of the tumor while in the “conservative” group less frequent evidence of hormones' deficiency has been registered. Once a residual lesions was observed a strict radiological follow-up is mandatory. Conclusions: According to dedicated literature and pre- and post-operative evidence of personal series, the authors try to provide an algorithm that could help in the standardization of the diagnostic and therapeutic pathways in patients with pituitary adenoma apoplexy.
Keywords: Pituitary adenoma; pituitary apoplexy; pituitary gland; transsphenoidal surgery